Embedded smart PZT-based sensor for internal damage detection in concrete under applied compression. (15th October 2020) - Kocherla, Amarteja; Subramaniam, Kolluru V.L.
Highlights: Embedded PZT sensor developed and used for Electrical impedance (EI) measurements from concrete. Internal cracking increases compliance and damping of concrete. EI signature changes with stress level in concrete. Applied stress and damage produce counteracting effects on EI measurement from sensor. Internal damage detected by PZT sensor significantly before visual observation on surface. Abstract: An embedded PZT-based sensor for monitoring internal damage in concrete is presented. An experimental program for producing controlled increments in levels of stress and damage in the concrete is developed. Formation and coalescence of microcracks are evaluated using digital image correlation. The electrical impedance (EI) measurements are recorded from the embedded sensor for different levels of stress and damage in the concrete. Changes in the EI signature associated with the resonant conditions of the PZT patch produced by stress and damage in the concrete are identified. The EI measurements provide a sensitive indication of the applied stress. Applied stress and damage in the concrete produce two counteracting effects on the EI resonant frequency. The internal damage in the concrete is detected from the EI measurement significantly earlier than the occurrence of surface cracking. Embedded sensors are more sensitive to the internal cracking in concrete compared to surface mounted PZT patches.